2009
DOI: 10.1016/j.jmaa.2009.03.047
|View full text |Cite
|
Sign up to set email alerts
|

A generalized circular summation of theta function and its application

Abstract: In this paper we prove a generalized Ramanujan's circular summation of theta function using the theory of elliptic and theta functions. This identity also includes a result of M. Boon, M.L. Glasser, J. Zar, I.J. Zucker and an addition formula of theta functions. Besides, we can get some new trigonometric identities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…When n = 4, taking y = π 8 , we also find sin 8 From Proposition 2.1, we can derive the following identity on circular summation of theta functions.…”
Section: Proposition 33 Suppose N Is a Positive Integer And Y Is A Rmentioning
confidence: 80%
See 1 more Smart Citation
“…When n = 4, taking y = π 8 , we also find sin 8 From Proposition 2.1, we can derive the following identity on circular summation of theta functions.…”
Section: Proposition 33 Suppose N Is a Positive Integer And Y Is A Rmentioning
confidence: 80%
“…3, using propositions in Sects. 1 and 2, we derive some new and nontrivial identities on circular summations of theta functions (see [1,8] …”
Section: Introductionmentioning
confidence: 99%
“…The first proof of the entire Theorem 1.1 was given by H. H. Chan, Z.-G. Liu and S. T. Ng [4], i.e., (12) and (13). By applying the Jacobi imaginary transformation to (12) Inspired by [4] and [3], X.-F. Zeng [17] proved the following important formula unifying Theorem 1.2 and 1.3 . Theorem 1.5.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In particular, with the theory of elliptic functions, the authors of [6] proved the following theta function identity, which is a dual form of the Ramanujan circular summation formula. (1.2) Motivated by [6] and [3], one former student of the second author, X.-F. Zeng [14], recently proved the following theorem, which unifies (1.1) and (1.2). Theorem 3.…”
mentioning
confidence: 96%
“…Different studies on the Ramanujan circular summation can be found in [1,[6][7][8]10,[12][13][14]. In particular, with the theory of elliptic functions, the authors of [6] proved the following theta function identity, which is a dual form of the Ramanujan circular summation formula.…”
mentioning
confidence: 99%